2018
DOI: 10.1080/17512433.2018.1519391
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C does not cause cardiovascular disease: a comprehensive review of the current literature

Abstract: For half a century, a high level of total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C) has been considered to be the major cause of atherosclerosis and cardiovascular disease (CVD), and statin treatment has been widely promoted for cardiovascular prevention. However, there is an increasing understanding that the mechanisms are more complicated and that statin treatment, in particular when used as primary prevention, is of doubtful benefit. Areas covered: The authors of three large reviews re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 106 publications
4
89
0
13
Order By: Relevance
“…Low or normal TC and LDL‐C in patients with CVD has been reported by other researchers 19,20 . Recently, the general view has been questioned 5‐7 . As reported by Ravnskov et al, 7 there are many observations and experiments contradicting that high TC or LDL‐C causes atherosclerosis and CVD, and several recent observations have supported their view.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Low or normal TC and LDL‐C in patients with CVD has been reported by other researchers 19,20 . Recently, the general view has been questioned 5‐7 . As reported by Ravnskov et al, 7 there are many observations and experiments contradicting that high TC or LDL‐C causes atherosclerosis and CVD, and several recent observations have supported their view.…”
Section: Discussionmentioning
confidence: 83%
“…In many studies, increased serum lipids and lipoproteins are associated with a higher risk of total and cardiac mortality 27‐35 . However, absence of an association, or even an inverse association, has been reported, 5‐7 especially with increasing age 26,36 . In accordance, prior observational studies have reported paradoxically better outcomes in hypercholesterolaemic patients who sustain acute coronary syndrome, the so‐called ‘cholesterol paradox’ 20,37‐39 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Focusing on plasma lipids, the positive association between total cholesterol (TC) and cardiovascular risk is strong in middle-aged adults, but it becomes weaker in those with 80 years of age or older (5). In addition, we recently reported that high LDL cholesterol (LDL-C) levels are not associated to subclinical coronary artery disease in healthy octogenarians (6) and results of a recent meta-analysis showed either a lack or an inverse association between LDL-C and both all-cause and CVD mortality in the late-life age (7).…”
Section: Introductionmentioning
confidence: 99%